Balancing Formalism and Justice An Analysis of Indonesian Mahkamah Agung’s Obscuur Libel Case Law in Light of ECtHR Standards - Surya, Axcelia Deandra (Universitas Airlangga, 2025)
Legal formalism plays a crucial role in ensuring consistency and predictability in judicial decision-making. However, excessive formalism can obstruct access to justice by prioritising procedural technicalities over substantive justice. This paper examines the Indonesian Supreme Court’s approach to Obscuur Libel cases where lawsuits may be dismissed due to failure to meet formal requirements. By analysing these decisions in light of the European Court of Human Rights (ECtHR) standards, this study explores the tension between procedural rigour and substantive justice. The paper assesses whether Indonesian case law aligns with ECtHR principles on fair trial rights and access to justice and identifies instances where excessive formalism may hinder judicial fairness. It further proposes guidelines to balance legal certainty with substantive justice, ensuring procedural fairness without unduly restricting legal remedies. By offering suggestions for enhancing procedural justice in Indonesia's legal system, this study adds to the larger conversation on judicial formalism and access to justice.